#TITLE_ALTERNATIVE# - HERU PRASETYO (NIM 15103011), MOHAMAD
Height of points above sea level or orthometric height H are usually determined by traditional levelling. This measurement technique requires a consistent reference surface. In the case of Total E&P Indonesie's field area in Mahakam Delta, East Kalimantan, traditional levelling might be difficult to be applied since the area consists of big rivers, swamps, hard access areas, etc. An alternative way to determine orthometric height in such an area is GPS levelling. Since GPS alone gives geodetic height or ellipsoidal height or height above reference ellipsoid h, geoid undulation information N in the whole area is required to convert geodetic height into orthometric height. In this thesis, Mahakam Delta local geoid model is completed by combination method from the local gravity data and global geopotensial model. The verification results present that the combination method produce more detail and accurate geoid model instead of using the global geopotensial model alone.